Five Level H-Bridge Configuration Based Microgrid with Sugeno Fuzzy Controller for New Energy Generation from Renewable Systems (2023)
Hybrid microgrids run by renewable energy sources are gaining popularity around the world. Solar (PV) and permanent magnet synchronous generator (PMSG) based wind energy systems (WES) are well-known and easy to install renewable energy options. Unfortunately, wind speeds and solar irradiance levels fluctuate unpredictably. Energy generation from both WES and PV panels must therefore fluctuate. Simultaneously, the load is fluctuating irregularly. Hence, storage devices must be incorporated into hybrid systems in order to keep the generation and consumption of electricity in equilibrium. In addition, for a fuel cell and electrolyzer that run on hydrogen, a tiny battery is added into the system to keep costs down. In order to enhance power quality and reliability, all the components in a microgrid need to be connected to an effective energy management system. For optimal use, renewable energy sources are combined with maximum power point trackers. When there are sudden shifts in both the energy supply and demand on a standalone microgrid, the energy balance and frequency response are crucial. In this study, a Takagi Sugeno based innovative fuzzy controller is implemented for a system to manage energy in order to achieve a precious and rapid reaction. The suggested system's Hardware-In-the-Loop is built using OPAL-RT modules in order to demonstrate detailed findings.